Measuring and Reducing The Travel-Related Carbon Footprint Of Sport Events In The Example Of Meo Rip Curl Portugal Pro 2023 - Zepf, Christoph Albrecht (2024)
This work explores the ecological dimensions of sporting events, with a primary focus on the MEO Rip Curl Portugal Pro 2023 as a case study. The main aim of this research is to calculate the travel-related carbon footprint of the event’s visitors and to investigate the potential for mitigating their carbon footprint. The research methodology comprises a quantitative survey questionnaire conducted among event attendees. The carbon footprint of various transportation modes was calculated using established emission factors. The study revealed that visitor travel constitutes a significant majority of the event's total carbon footprint. Additionally, it identified the need for enhanced efforts in promoting environmental-friendly transportation options. Finally, an all-encompassing carbon footprint reduction plan was devised to provide event managers with recommendations to mitigate the carbon footprint associated with their events. This work underscores the important role of sports events in environmental education and advocacy. It highlights the importance of measuring, reducing, and mitigating carbon footprints, especially in the context of event visitor travel. The findings emphasise the potential for sports events to adopt more environmental-friendly practices and contribute to global environmental goals. Overall, this research calls for increased awareness and action towards a more eco-conscious sports industry.